Sintering of GGAG:Ce3+, xY3+ transparent ceramics in oxygen atmosphere. Issue 17 (1st December 2017) - Zhang, Ji-Yun; Luo, Zhao-Hua; Jiang, Hao-Chuan; Jiang, Jun; Gui, Zhen-Zhen; Chen, Chun-Hua; Liu, Yong-Fu; Liu, Shuang; Ci, Meng-Meng
Abstract: Cerium doped gadolinium gallium aluminum garnet ceramics (GGAG:Ce) have promising applications such as medical imaging, high power WLEDs and other high energy radiation detection due to their excellent and unique combination of chemical and physical properties. Partial substitution of gadolinium with yttrium can improve some of the optical and scintillation properties even further. The goal of this work is to research the effect of Y 3+ to the sintering of GGAG ceramics. The optical transmittance, micro-structure and grain growth kinetics have been investigated. This research indicates that the doping of Y 3+ ion would transfer the main sintering mechanism for grain growth from solid state mass transport to liquid phase mass transport, thereby reducing the activation energy of the sample.